Dual curing adhesive composition comprising block copolymer

By using block copolymers of (meth)acrylate-based hard segments and urethane-based soft segments in the adhesive, combining the dual curing reaction of heat and light, the existing adhesives have been solved in the high-temperature treatment and miniaturization modules, and the dual effects of high adhesion and impact resistance are achieved.

CN119552582APending Publication Date: 2025-03-04ENF TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410703297.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-04
Filing Date
2024-06-03
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing adhesive tends to cause thermal damage to image sensors and the like during high temperature treatment, and it is difficult to meet excellent adhesion, impact resistance and generation efficiency requirements in miniaturized and thinner camera modules.

Method used

A double curing adhesive composition containing a block copolymer of a (meth)acrylate-based hard segment and a urethane-based soft segment is used to form a high-performance adhesive layer through a dual curing reaction of heat and light.

Benefits of technology

It realizes excellent adhesion and excellent impact resistance even in a small amount, and is suitable for the adhesive layer between components such as miniaturized and thinner camera modules.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552582A_ABST
    Figure CN119552582A_ABST
Patent Text Reader

Abstract

The present invention relates to a dual curable adhesive composition comprising a block copolymer. The adhesive composition has an excellent impact resistance improving effect while having an excellent adhesive force, and can improve the impact resistance through the achievement of the physical properties as described above. This adhesive layer can be usefully applied to an adhesive layer between members such as a miniaturized and thinned camera module that requires excellent adhesive force even when used in a small amount and also requires durability and impact resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a dual-cure adhesive composition comprising a block copolymer. Background Art

[0002] A dual-cure adhesive of the type that performs main curing by heat after pre-curing by light irradiation is proposed for an adhesive used for assembling a camera module in order to minimize thermal damage to an image sensor or the like caused by high-temperature processing and satisfy adhesion, reliability, and production efficiency.

[0003] Furthermore, as camera modules have been recently miniaturized and thinned, components of camera modules have also become finer, and thus the performance required of adhesives for bonding and fixing the components has gradually become more complex. As an example, as camera modules have been recently miniaturized and thinned, components of camera modules have also become finer, and thus the performance required of adhesives for bonding and fixing the components has gradually become more complex.

[0004] In particular, as mobile camera modules are miniaturized, the amount of adhesive required for assembling camera modules is reduced, and thus only a small amount of adhesive should be used to meet the same physical properties as before, and an adhesive with better performance than before is required. In addition, although mobile camera modules are developing with a trend of reducing the modulus of the adhesive to improve impact resistance, an adhesive with a low modulus will cause a fatal problem of being weak to heat resistance and having reduced adhesive force.

[0005] Therefore, there is a need for an adhesive which does not decrease the modulus even with a small coating amount and has high impact resistance while having excellent adhesive force. Summary of the invention

[0006] Technical issues to be solved

[0007] One aspect of the present invention is a dual-cure adhesive composition that has excellent adhesion and outstanding impact resistance even when used in a small amount.

[0008] Means of solving the problem

[0009] The present invention provides an adhesive composition comprising a block copolymer containing a (meth)acrylate hard segment and a urethane soft segment.

[0010] According to one embodiment of the present invention, the (meth)acrylate based hard segment may contain repeating units derived from C1-7 alkyl (meth)acrylate based monomers.

[0011] According to an embodiment of the present invention, the number average molecular weight (Mn) of the (meth)acrylate hard segment may be 20k to 500 kg / mol.

[0012] According to one embodiment of the present invention, the urethane soft segment may contain repeating units derived from polyether polyols.

[0013] According to an embodiment of the present invention, the number average molecular weight (Mn) of the urethane soft segment may be 1000 to 5000 g / mol.

[0014] According to one embodiment of the present invention, the block copolymer may be a triblock copolymer or a multiblock copolymer including two or more hard segments.

[0015] According to one embodiment of the present invention, the block copolymer may include 0.1 to 20 wt % relative to the total weight of the composition.

[0016] According to an embodiment of the present invention, the adhesive composition may further include a base epoxy resin and a curing agent.

[0017] According to an embodiment of the present invention, the adhesive composition may further include a multifunctional monomer and a photoinitiator.

[0018] According to an embodiment of the present invention, the multifunctional monomer may be a multifunctional acrylic compound, a thiol compound or a combination thereof.

[0019] According to an embodiment of the present invention, the adhesive composition may be a dual-curing type.

[0020] The present invention can provide a cured product prepared from the above-mentioned adhesive composition.

[0021] Effects of the Invention

[0022] According to one aspect, the adhesive composition has excellent adhesion and an excellent effect of improving impact resistance, and by achieving the physical properties as described above, it can be usefully applied to the adhesive layer between components of miniaturized and thinned camera modules, etc., which require excellent adhesion even when used in small amounts and also require durability and impact resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The method for preparing samples for evaluation of adhesion and impact resistance is shown.

[0024] Figure 2 The impact resistance evaluation method is shown. DETAILED DESCRIPTION

[0025] Hereinafter, the present invention will be described in more detail by specific examples or embodiments including the accompanying drawings. However, the following specific examples or embodiments are only a reference for describing the present invention in detail, and the present invention is not limited thereto and can be limited to various forms.

[0026] Unless otherwise defined in this specification, all technical terms and scientific terms have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used for explanation in this specification are only used to effectively record specific examples and are not intended to limit the present invention.

[0027] Unless the context specifically indicates otherwise, the singular form used in the present specification may be intended to include the plural form as well.

[0028] In addition, units used in this specification unless otherwise specified are based on weight, and as an example, a unit of % or ratio means weight % or weight ratio, and unless otherwise defined, weight % means the weight % of any one component in the entire composition in the composition.

[0029] In addition, the resin range used in this specification includes the lower limit value and the upper limit value and all values ​​within the range, increments logically derived from the form and width of the defined range, all values ​​of the double definition, and all possible combinations of the upper and lower limits of the numerical range defined in different forms from each other. Unless otherwise specifically defined in this specification, values ​​outside the numerical range that may appear due to experimental errors or numerical rounding are also included in the defined numerical range.

[0030] The term “comprising” in this specification is an open-ended description having a meaning equivalent to expressions such as “having”, “containing”, “having” or “characterized by”, and does not exclude elements, materials or processes that are not additionally listed.

[0031] The term "alkyl" in this specification refers to an organic free radical derived from an aliphatic hydrocarbon by removing one hydrogen, and may include both straight-chain and branched forms. As an example, it includes methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, hexyl, ethylhexyl, etc., but is not limited thereto.

[0032] The "alicyclic" described in the present invention as a cycloalkyl group means a non-aromatic monocyclic or multicyclic ring system having 3 to 10 carbon atoms and may have an unsaturated bond in the ring.

[0033] The term "(meth)acrylate system" in this specification includes both acrylate systems and methacrylate systems.

[0034] The "epoxy resin" described in the present invention means a cured plastic that has completed a reaction with a curing agent in an academic sense, but as generally used in the technical field, it becomes a raw material of an epoxy composition, and because it has an epoxy group, it can mean an epoxy compound that can react with a curing agent.

[0035] In addition, the "cured product" described in the present invention has a general meaning and may be a cured product generated by curing the adhesive composition. In addition, the cured product may include a semi-cured product.

[0036] Hereinafter, one aspect of the present invention will be described in more detail.

[0037] The present invention provides an adhesive composition comprising a block copolymer containing a (meth) acrylate hard segment and a urethane soft segment. The block copolymer is a copolymer comprising two or more regions or segments (segment, or block) of chemical distinctions connected in a linear manner (or, covalently bonded), and contains a hard segment (Hard segment) and a soft segment (Soft segment). As an example, the block copolymer may be a triblock copolymer or a multiblock copolymer comprising two or more hard segments, and the block copolymer may be formed in the form of AB, ABA, BAB or ABAB, but is not limited thereto. At this time, A is a hard segment (Hard segment), and B is a soft segment (Soft segment).

[0038] According to one embodiment of the present invention, the hard segment may include a (meth)acrylate hard segment, and the (meth)acrylate hard segment may contain repeating units derived from alkyl (meth)acrylate monomers or repeating units derived from alkyl (meth)acrylate copolymers. The alkyl (meth)acrylate monomer may be C 1-15 Alkyl (meth) acrylate monomers, C 1-7 Alkyl (meth) acrylate monomer or C 1-3 The alkyl (meth)acrylate monomer may be, for example, one or more selected from methyl acrylate, ethyl acrylate, n-butyl acrylate, tert-butyl acrylate, and the like.

[0039] According to one embodiment of the present invention, the alkyl (meth) acrylate monomer or alkyl (meth) acrylate copolymer may contain a functional group reactive with isocyanate at the end, specifically, any one functional group selected from hydroxyl group and thiol group, etc. As a non-limiting example, the alkyl (meth) acrylate copolymer may be provided with a functional group at the end by a method of treating the alkyl (meth) acrylate monomer with an initiator that protects the functional group during polymerization, and then treating the alkyl (meth) acrylate monomer with an acid, or by a method of copolymerizing a second monomer containing any one functional group selected from hydroxyl group and thiol group, etc. with the alkyl (meth) acrylate monomer, but is not limited thereto, and conventional or well-known methods may be used without limitation.

[0040] According to still another embodiment of the present invention, the alkyl (meth)acrylate-based copolymer may contain a hydroxyl group only at one end.

[0041] As an example, the second monomer may be any one selected from 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 2-hydroxyethylene glycol (meth)acrylate and 2-hydroxypropylene glycol (meth)acrylate, but is not limited thereto.

[0042] According to one embodiment of the present invention, the number average molecular weight (Mn) of the (meth)acrylate hard segment may be 20k to 500kg / mol, 50k to 400kg / mol, 80k to 350kg / mol, or 100k to 300kg / mol. In addition, the polydispersity index (PDI) of the (meth)acrylate hard segment may be 3.0 or less, 2.0 or less, 1.0 to 2.0, or 1.0 to 1.5, but is not limited thereto.

[0043] According to one embodiment of the present invention, the soft segment may include a urethane soft segment, and the urethane soft segment may contain a repeating unit derived from a polyol and a repeating unit derived from a diisocyanate compound. Specifically, the urethane soft segment may be a repeating unit derived from a urethane prepolymer containing a urethane coupling group formed by the reaction of a polyol and a diisocyanate compound. In addition, the ratio of the polyol to the diisocyanate compound is 1:0.5 to 5, 1:0.8 to 2, or 1:0.9 to 1.1. Alternatively, compared with the polyol, an excess of diisooctanoate compounds may be included, and specifically, the reaction may be carried out in a molar ratio of 1:1.1 to 5, 1:1.2 to 4, 1:1.5 to 4, or 1:1.8 to 3, and the urethane prepolymer may contain isocyanate groups at both ends.

[0044] According to an embodiment of the present invention, the polyol may be a polyester polyol, a polyether polyol or a combination thereof. As a non-limiting example of the polyol, one or more polyols selected from ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 1,4-butene glycol, 1,4-butynediol, 1,5-pentanediol, neopentyl glycol, bis(hydroxymethyl)cyclohexane, 2-methyl-1,3-propanediol, methylpentanediol, diethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol, dipropylene glycol, polypropylene glycol, dibutylene glycol, polybutylene glycol, polytetramethylene ether glycol (PTMEG), polyhexamethylene ether glycol (PHMEG), polycarbonate diol and polycaprolactone diol can be used, and specifically, polyethylene glycol, polypropylene glycol, polybutylene glycol, polytetramethylene ether glycol (PTMEG), polyhexamethylene ether glycol (PHMEG), polycarbonate diol and polycaprolactone diol can be used. Preferably, a polyether polyol having a number average molecular weight of 200 to 8000 g / mol, 500 to 5000 g / mol, 800 to 3500 g / mol, or 1200 to 2500 g / mol may be used.

[0045] According to one embodiment of the present invention, the diisocyanate compound can be selected from aliphatic diisocyanate compounds, alicyclic diisocyanate compounds, aromatic diisocyanate compounds and polyisocyanates. As non-limiting examples of the diisocyanate compound, tri-, tetra-, penta-, hexa-, hepta- or octa-methylene diisocyanate, 2-methylpentamethylene 1,5-diisocyanate, 2-ethyltetramethylene 1,4-diisocyanate, hexamethylene 1,6-diisocyanate (HDI), pentamethylene 1,5-diisocyanate, 1,4-butyl diisocyanate, trimethylhexamethylene 1,6-diisocyanate, isophorone diisocyanate (IPDI), 1,4- or 1,3-bis(isocyanatemethyl)cyclohexane (HXDI), cyclohexane 1,4-diisocyanate, 1-methylcyclohexane 2,4- or 2,6-diisocyanate, methylene dicyclohexane The present invention may be used in combination with one or more diisocyanate compounds selected from the group consisting of methyl (4,4'-, 2,4'- or 2,2'-) diisocyanate (H12MDI), naphthalene 1,5-diisocyanate (NDI), toluene 2,4- or 2,6-diisocyanate (TDI), 3,3'-dimethyl-4,4'-diisocyanate biphenyl (TODI), p-phenylene diisocyanate (PDI), diphenylethane 4,4'-diisocyanate (EDI), diphenylmethane diisocyanate, dimethyl diphenyl 3,3'-diisocyanate, diphenylethane 1,2-diisocyanate, diphenylmethane diisocyanate (MDI), and polyisocyanate, but is not limited thereto, and commercially available products may be used without limitation. Preferably, C 6-15 Alicyclic diisocyanate compounds.

[0046] According to one embodiment of the present invention, the urethane soft segment may have a structure in which isocyanate is included at both ends of a polyol molecule, or a structure in which a plurality of polyol molecules form urethane bonds with a diisocyanate compound and include isocyanate at both ends of the soft segment.

[0047] According to an embodiment of the present invention, the number average molecular weight (Mn) of the urethane soft segment may be 500 to 8000 g / mol, 500 to 6000 g / mol, 800 to 4000 g / mol or 2000 to 3000 g / mol.

[0048] According to one embodiment of the present invention, the block copolymer can be prepared by subjecting an alkyl (meth) acrylate monomer or alkyl (meth) acrylate copolymer (hereinafter referred to as A) containing a functional group that can react with isocyanate to a urethane reaction with an urethane prepolymer (hereinafter referred to as B) having isocyanate at both ends. Although the molar ratio of the components can be easily adjusted to suit the intended use, in order to improve impact resistance, the molar ratio of A to B may satisfy 1 to 5:1 or 1.5 to 3:1. In addition, the equivalent ratio of the functional group contained in A to the isocyanate group contained in B may be 0.5 to 3:1 or 0.8:1.5:1.

[0049] According to one embodiment of the present invention, the block copolymer may contain 0.1 to 20 parts by weight, 0.1 to 10 parts by weight, 0.3 to 5 parts by weight, or 0.3 to 1 parts by weight of the soft segment relative to 100 parts by weight of the hard segment. At this time, the weight can be calculated based on the number average molecular weight of each segment, and the number average molecular weight can be defined as a value measured by gel permeation chromatography using polystyrene as a standard sample.

[0050] According to one embodiment of the present invention, the number average molecular weight (Mn) of the block copolymer may be 50k to 1000 kg / mol, 50k to 800 kg / mol, 80k to 700 kg / mol or 100k to 500 kg / mol.

[0051] According to one embodiment of the present invention, the block copolymer may include 0.1 to 50 wt %, 0.1 to 20 wt %, or 1 to 10 wt % relative to the total weight of the composition.

[0052] According to one embodiment of the present invention, the block copolymer connects the urethane soft segment and the (meth)acrylate hard segment through urethane bonding, which can promote interactions such as hydrogen bonding inside or with other components of the adhesive composition, and thereby can prepare an adhesive composition that has excellent durability and impact resistance while having excellent adhesion even when used in small amounts.

[0053] According to an embodiment of the present invention, the adhesive composition may further include a base epoxy resin and a curing agent, and optionally, may further include a curing accelerator.

[0054] According to an embodiment of the present invention, the block copolymer may be included in an amount of 1 to 50 parts by weight, 5 to 40 parts by weight, or 10 to 30 parts by weight relative to 100 parts by weight of the base epoxy resin.

[0055] The base epoxy resin may be used without limitation as long as it is commonly used in the art, and may be an aliphatic epoxy compound, an alicyclic epoxy compound, or an aromatic epoxy compound, specifically, triglycidyl ether or diglycidyl ether, but is not limited thereto.

[0056] As an example, the base epoxy resin may include any one or more bisphenol epoxy resins selected from bisphenol A series, bisphenol E series, bisphenol F series, bisphenol M series, bisphenol S series, and bisphenol H series, etc.; one or more mixtures selected from glycidyl ether epoxy resins, glycidyl amine epoxy resins, novolac epoxy resins, and cresol novolac epoxy resins, etc. As an example, bisphenol A diglycidyl ether, bisphenol F diglycidyl ether, bisphenol S diglycidyl ether, brominated bisphenol A diglycidyl ether, brominated bisphenol F diglycidyl ether, brominated bisphenol S diglycidyl ether, etc. may be listed, but are not limited thereto. In addition, the base epoxy resin may be liquid at room temperature, and the epoxy equivalent (EEW) may be 100 to 600 g / eq or 150 to 500 g / eq.

[0057] In addition, the base epoxy resin may be included in an amount of 5 to 80 wt %, 10 to 60 wt %, or 15 to 50 wt % relative to the entire weight of the adhesive composition.

[0058] The curing agent can use commonly used solid curing agents and liquid curing agents, and the curing agent can directly participate in the crosslinking of the composition or can be used in the form of a catalyst. The curing agent can be an amine curing agent, an acid anhydride curing agent or a phenol curing agent. These can be used alone or in combination of two or more. Preferably, an amine curing agent can be used. As an example, commercially available products such as Adeka EH-4357S, Adeka Hardener EH-4357S, AdekaHardener EH-4357PK, Adeka Hardener EH-4380S, Fujicure FXR-1081, Fujicure FXR-1020, Sunmide LH-210, Sunmide LH-2102, Sunmide LH-2100, Ajicure PN-23, Ajicure PN-F, Ajicure PN-23J, Ajicure PN31, Ajicure PN-31J, Novacure HX-3722, Novacure HX-3742, Novacure HX-3613 and Asahi Kasei Chemicals HX3932HP can be used, but are not limited thereto.

[0059] Examples of the amine curing agent include dimethyldioxane, dicyandiamide, isophoronediamine, diethylenetriamine, triethylenetetramine, triethylenepentamine, bis(p-aminocyclohexyl)methane, methylenedianiline (e.g., 4,4'-methylenedianiline), 4,7,10-trioxotridecane-1,13-diamine, polyetheramine (e.g., Jeffamine D-230, JeffamineD-400, etc.), diaminodiphenylmethane, diaminodiphenyl sulfone, 2,4-toluenediamine, 2,6-toluenediamine, 2,4-diamino-1-methylcyclohexane, 2,6-diamino-1-methylcyclohexane, 2,4-diamino-3,5-diethyltoluene, 2,6-diamino-3,5-diethyltoluene, 1,2-diaminobenzene, 1,3-diaminobenzene, 1,4-diaminobenzene, diaminodiphenyl ether, 3,3',5,5'-tetramethyl-4,4'-diaminobiphenyl and 3,3'-dimethyl-4,4'-diaminobiphenyl, etc.

[0060] Examples of the acid anhydride curing agent include phthalic anhydride, maleic anhydride, trimellitic anhydride, pyromellitic anhydride, hexahydrophthalic anhydride, tetrahydrophthalic anhydride, methylnadic anhydride, nadic anhydride, glutaric anhydride, methylhexahydrophthalic anhydride, and methyltetrahydrophthalic anhydride.

[0061] Examples of the phenolic curing agent include phenolic resins such as formaldehyde condensation type resol type phenolic resins, formaldehyde-free condensation type phenolic resins, novolac type phenolic resins, novolac type phenolic resins and polyhydroxystyrene resins; resol type phenolic resins such as aniline modified novolac phenolic resins and melamine modified novolac phenolic resins; novolac type phenolic resins such as phenol novolac resins, cresol novolac resins, tert-butylphenol novolac resins, nonylphenol novolac resins and naphthol novolac resins; special phenolic resins such as dicyclopentadiene modified phenolic resins, terpene modified phenolic resins, trisphenol methane type resins, phenol aralkyl resins having a phenylene skeleton or a diphenylene skeleton, and naphthol aralkyl resins; and polyhydroxystyrene resins such as poly(p-hydroxystyrene).

[0062] In addition, the curing agent may be included in an amount of 1 to 100 parts by weight, 5 to 80 parts by weight based on 100 parts by weight of the base epoxy resin included in the adhesive composition, but is not limited thereto.

[0063] The curing accelerator is used to adjust the curing speed, and at least one selected from imidazole-based accelerators and urea-based accelerators can be used.

[0064] Examples of the imidazole accelerator include 2-methylimidazole, 2-heptadecylimidazole, 2-phenylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 2-ethyl-4-methylimidazole, 2-methylimidazole, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2-undecylimidazole, 3-heptadecylimidazole, 2-phenylimidazole, 2-phenylimidazoline, 1,2-dimethylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole and 1-cyanoethyl-2-undecylimidazole, but are not limited thereto.

[0065] Examples of the urea-based accelerator include p-chlorophenyl-N,N-dimethylurea, 3-phenyl-1,1-dimethylurea, and 3,4-dichlorophenyl-N,N-dimethylurea, but are not limited thereto.

[0066] In addition, the curing accelerator may be included in an amount of 0.1 to 100 parts by weight, 5 to 80 parts by weight based on 100 parts by weight of the base epoxy resin included in the adhesive composition, but is not limited thereto.

[0067] According to an embodiment of the present invention, the adhesive composition may further include a multifunctional monomer and a photoinitiator. The multifunctional monomer may be a multifunctional acrylic compound, a thiol compound or a combination thereof.

[0068] In addition, the multifunctional monomer may be included in an amount of 1 to 80 wt %, 5 to 60 wt %, or 10 to 40 wt % relative to the total weight of the adhesive composition.

[0069] The multifunctional acrylic compound can be used without much restriction as long as it is a compound containing two or more or three or more acrylic groups, and as an example, it can be one or more selected from dipentaerythritol hexa(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, trimethylolpropane tri(meth)acrylate, glycerol tri(meth)acrylate, tri[2-(acryloyloxy)ethyl]isocyanurate, di-trimethylolpropane tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate and pentaerythritol tetra(meth)acrylate, but is not limited thereto.

[0070] In addition, the multifunctional acrylic compound may be included in an amount of 1 to 90 wt %, 5 to 50 wt %, or 5 to 30 wt % relative to the total weight of the adhesive composition.

[0071] As long as it is a compound containing two or more or three or more thiol groups, the thiol compound can be used without much restriction, and as an example, it can be one or a combination of two or more selected from 1,4-bis(3-mercaptobutyryloxy)butane, 1,3,5-tris(3-mercaptobutoxyethyl)-1,3,5-triazine 2,4,6(1H,3H,5H)-trione, trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptobutyrate), pentaerythritol tris(3-mercaptobutyrate), pentaerythritol tetrakis(3-mercaptopropionate), dipentaerythritol hexa(3-mercaptopropionate) and tetraethylene glycol bis(3-mercaptopropionate), but is not limited thereto.

[0072] In addition, the thiol compound may be included in an amount of 1 to 90 wt %, 5 to 50 wt %, or 5 to 30 wt % relative to the total weight of the adhesive composition.

[0073] According to an embodiment of the present invention, the multifunctional monomer may be included in an amount of 10 to 200 parts by weight, 20 to 120 parts by weight, or 50 to 100 parts by weight relative to 100 parts by weight of the base epoxy resin.

[0074] The photoinitiator may be used without limitation as long as it is common, and examples thereof include benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin n-butyl ether, benzoin isobutyl ether, acetophenone, hydroxydimethylacetophenone, dimethylaminoacetophenone, dimethoxy-2-phenylacetophenone, 3-methylacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 4-chlorophenolacetophenone, 4,4-dimethoxyacetophenone, 2-hydroxy-2-methyl-1-phenylpropane-1-one, 4-hydroxycyclophenyl ketone, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholine-propane-1-one, 4-(2-hydroxyethoxy)- )phenyl-2-(hydroxy-2-propyl)ketone, benzophenone, p-phenylbenzophenone, 4,4-diaminobenzophenone, 4,4'-diethylaminobenzophenone, dichlorobenzophenone, anthraquinone, 2-methylanthraquinone, 2-ethylanthraquinone, 2-tert-butylanthraquinone, 2-aminoanthraquinone, β-chloroanthraquinone, 2-methylthioxanthone, 2-ethylthioxanthone, 2-chlorothioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, benzyl dimethyl ketal, diphenyl ketone benzyl dimethyl ketal, acetophenone dimethyl ketal, p-dimethylaminobenzoate, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, fluorene, triphenylamine, carbazole, benzyl diphenyl sulfide and tetramethylthiuram monosulfide, and one or a mixture of two or more selected from them can be used. In addition, commercially available products such as Darocur 1173, Igacure 184, and Igacure 907 (Ciba) are exemplified.

[0075] In addition, the photoinitiator may be included in an amount of 0.01 to 20 parts by weight, 0.1 to 10 parts by weight based on 100 parts by weight of the multifunctional monomer included in the adhesive composition, but is not limited thereto.

[0076] The inorganic filler can be used without restriction as long as it is common, and as its non-limiting examples, silicon dioxide, diatomaceous earth, aluminum oxide, zinc oxide, iron oxide, magnesium oxide, tin oxide, titanium oxide, magnesium hydroxide, aluminum hydroxide, magnesium carbonate, barium sulfate, gypsum, calcium silicate, talc, glass beads, sericite, talcum clay, bentonite, aluminum nitride, silicon nitride, potassium titanate, zeolite, calcium oxide, magnesia and ferrite, etc., and can be used as a mixture of one or more selected from them. Here, the inorganic filler can be included as 10 to 60 weight %, 15 to 50 weight %, 25 to 40 weight % based on the total weight of the adhesive composition. Alternatively, the inorganic filler can be included as 10 to 200 weight parts, 50 to 180 weight parts or 120 to 160 weight parts relative to 100 weight parts of the base epoxy resin.

[0077] The adhesive composition according to one embodiment of the present invention may include a block copolymer, a basic epoxy resin, a curing agent, a multifunctional monomer, a photoinitiator and an inorganic filler. Specifically, the dual-curing adhesive composition may include 0.1 to 50% by weight of a block copolymer, 5 to 80% by weight of a basic epoxy resin, 1 to 30% by weight of a curing agent, 1 to 80% by weight of a multifunctional monomer, 0.1 to 10% by weight of a photoinitiator and 5 to 60% by weight of an inorganic filler, or 0.1 to 20% by weight of a block copolymer, 10 to 60% by weight of a basic epoxy resin, 1 to 25% by weight of a curing agent, 5 to 60% by weight of a multifunctional monomer, 0.5 to 5% by weight of a photoinitiator and 15 to 50% by weight of an inorganic filler relative to the overall weight of the adhesive composition.

[0078] In addition, any one or more other additives can also be added to the adhesive composition according to an embodiment of the present invention. For example, any additive can also include stabilizer, viscosity modifier, surfactant, pigment or dye, matting agent, flame retardant, curing inhibitor, defoamer, wetting agent, colorant, thermoplastic agent, processing aid, ultraviolet (UV) blocker, fluorescent compound, UV stabilizer, antioxidant, release agent and their mixture. The arbitrary additive can be used in the scope of the physical property of the adhesive composition of the present invention without hindering.

[0079] According to one embodiment of the present invention, the adhesive composition may be a one-component type or a two-component type, and may be usefully applicable as a structural adhesive. In addition, the adhesive composition may be a dual-curing adhesive composition. Specifically, the adhesive composition may form a first polymer network derived from a photopolymerizable multifunctional monomer by thermal curing and photocuring reactions, and form a second polymer network derived from a curing agent and an epoxy resin. The first polymer network and the second polymer network may densely form an interpenetrating polymer network (IPN) that is physically mixed and interpenetrated, thereby imparting high bonding strength and excellent impact resistance. Thus, the adhesive composition may not only be implemented by selecting photocuring, thermal curing or making it parallel dual curing according to the use environment or purpose, but may also be implemented by simultaneously realizing the bonding force and impact resistance of dual curing even if used in small quantities with the block copolymers described above.

[0080] Although the adhesive composition according to one aspect has low viscosity before the curing reaction, after the primary curing reaction of the photocuring reaction, the viscosity increases sharply by forming the first polymer network. Thus, an adherend such as a camera module can be reliably supported on the substrate, and as the IPN is formed by the subsequent thermal curing reaction, the adherend can be firmly bonded and fixed on the substrate and can have excellent durability and reliability.

[0081] The photocuring can be performed under normal photocuring conditions and can be performed by irradiating a light source such as infrared rays, visible light, ultraviolet rays, electron rays, etc. having a wavelength of 800 nm or more, and the light source can be 100 to 3000 mW / cm 2 , 300 to 3000mW / cm 2 or 500 to 2000 mW / cm 2 The range is 1 to 20 seconds or 1 to 10 seconds. In addition, the light source irradiation means can include low-pressure mercury lamp, medium-pressure mercury lamp, high-pressure mercury lamp, ultra-high-pressure mercury lamp, excimer laser, chemical lamp, black light lamp, microwave excitation mercury lamp, metal halide lamp, sodium lamp, fluorescent lamp, LED SPOT type UV irradiator, xenon lamp, 365nm wavelength ultraviolet lamp or deep ultraviolet lamp, but are not limited thereto.

[0082] The thermal curing may be performed under conventional epoxy thermal curing conditions, and as an example, may be performed at a temperature of less than 150°C, less than 100°C, less than 90°C, or between 50 and 90°C for less than 6 hours, between 10 minutes and 5 hours, or between 30 minutes and 2 hours.

[0083] The present invention can provide a block copolymer comprising a urethane-based soft segment and containing a (meth)acrylate-based hard segment at both ends. Since the block copolymer according to one embodiment is the same as the description of the block copolymer, a detailed description thereof is omitted.

[0084] According to one embodiment, when one segment is a unit segment, the weight ratio of the urethane soft unit segment to the (meth)acrylate hard unit segment may be 1:5-200, 1:10-150 or 20-100.

[0085] The present invention may provide a toughening agent for epoxy adhesives including the block copolymer. The block copolymer according to one embodiment may be provided as an additive for improving the impact resistance of the epoxy adhesive composition, specifically, a toughening agent.

[0086] The present invention can provide a cured product prepared from the above-mentioned adhesive composition. The cured product can have excellent adhesion even if only a small amount is used and achieves improved impact resistance and reliability. In this regard, the cured product according to one aspect can be usefully used as an adhesive, a sealant, a coating agent, etc. Specifically, it can be usefully applied as an adhesive layer between components such as camera modules that require high bonding strength and impact resistance per unit area, and can be used as a structural adhesive not only in structures such as civil engineering and construction but also in the assembly of means of transportation such as automobiles, airplanes, and ships. This can be used in a variety of ways across industries by achieving excellent bonding properties between the same or different materials such as metal and metal, metal and glass, metal and carbon fiber, etc.

[0087] In addition, one aspect of the present invention provides a structure including the cured product. Specifically, the structure according to one aspect may include a first adherend, a second adherend, and an adhesive layer disposed between the first adherend and the second adherend, and the adhesive layer may be the cured product.

[0088] As an example, the first adherend and the second adherend may be parts of aluminum, brass or polycarbonate, etc. Specifically, the first adherend and the second adherend may be selected from lenses, lens holders and housings, etc., and part or the whole of them may be bonded with high bonding strength through the above-mentioned bonding layer to form a high-quality structure.

[0089] Specifically, the structure according to one aspect may be a camera module.

[0090] As an example, the structure may be a camera module mounted on a mobile device such as a smartphone, or a camera module for a vehicle.

[0091] The above implementation examples are described in more detail below through embodiments. However, the following embodiments are only for illustrative purposes and do not limit the scope of rights.

[0092] [Physical property evaluation method]

[0093] 1. Molecular weight and polydispersity index (PDI)

[0094] The measurement was performed using the gel permeation chromatography (GPC) method of Waters. The chromatograph used GF-801, GF-802, and GF-804 of Shodex, the standard sample used polystyrene of Shodex, the solvent used tetrahydrofuran, and the number average molecular weight (Mn) and polydispersity index (PDI) were measured at a temperature of 40° C. and a flow rate of 1.0 mL / min.

[0095] 2. Storage stability

[0096] The adhesive compositions of the examples and comparative examples were stored in a plastic sealed container at 25° C. for 72 hours, and the viscosity before and after storage was measured, and the storage stability was evaluated based on the following criteria, and the results are recorded in the following Table 2. At this time, the viscosity was measured using an HBDV-2T viscosity analyzer under the measurement conditions of 25° C., spindle SC4-14, and Rpm 5.0.

[0097] X: Increased by more than 20% compared to the initial viscosity

[0098] O: Less than 20% increase compared to initial viscosity

[0099] 3. Adhesion

[0100] The adhesive composition of the embodiment and the comparative example (discharge amount: 50 mg) was dispensed into a form with an inner diameter of 13.5 mm and an outer diameter of 15.5 mm at the aluminum first adherend interface. Subsequently, the unit was prepared by bonding with the aluminum second adherend (refer to Figure 1 ). At this time, the spacing between the first adherend and the second adherend was 300 μm. Subsequently, the prepared unit was cured for the first time using four light sources (1000 mW / cm2) while keeping the distance between the ultraviolet light of LED 365 nm and the adhesive composition and the light source at 25 mm in the horizontal direction of the unit. 2 , 7s), and then heated in a convection oven at 80°C for 1 hour and subjected to a second curing.

[0101] Subsequently, the adhesive force of the cured unit was measured using UTM (AMETEK LD50), and the tensile speed was set to 30 mm / min. The results are shown in Table 2 below.

[0102] 4. Impact resistance evaluation

[0103] The samples were prepared in the same manner as for the unit used to measure adhesion. Figure 2 As shown in , the sample was freely dropped from a height of 1 m onto the bottom of a stainless steel plate (SUS plate) multiple times, and the number of drops when the aluminum first adherend was separated from the second adherend was measured. The number of drops of five samples prepared in the same manner was measured, and the average number was recorded in the following Table 2.

[0104] [Manufacturing Examples 1-1 to 1-3] Preparation of Hard Segments

[0105]

[0106] After anionic polymerization of methyl methacrylate monomer at -40°C using an initiator in which a functional group is protected, polymethyl methacrylate having hydroxyl terminal groups was synthesized by acid treatment.

[0107] At this time, the hard segments according to the respective manufacturing examples 1-1, 1-2 and 1-3 were prepared by adjusting the content of the initiator to 0.1 wt%, 0.2 wt%, and 0.3 wt% per 1 mol of the methyl methacrylate monomer, and the number average molecular weight of each hard segment was measured to be 152300 g / mol, 108000 g / mol, and 52000 g / mol, and the polydispersity index was measured to be 1.2.

[0108] [Manufacturing Examples 2-1 to 2-3] Preparation of Soft Segments

[0109]

[0110] In a reactor, 1 mol of poly(tetramethylene ether) glycol (PTMEG) as a polyol and 2 mol of isophorone diisocyanate (IPDI) as a diisocyanate were dissolved in 500 g of methyl ethyl ketone (MEK), and then 0.1 g of a catalyst dibutyltin dilaurate (DBDTL) was added, and the mixture was stirred at room temperature (25° C.) for 24 hours to prepare a urethane soft segment with isocyanate at both ends.

[0111] At this time, polyols with number average molecular weights of 1000 g / mol, 2000 g / mol and 3000 g / mol were added to prepare soft segments according to respective manufacturing examples 2-1, 2-2 and 2-3, and the number average molecular weights of the respective soft segments were measured to be 1200 g / mol, 2500 g / mol and 3600 g / mol, respectively.

[0112] [Manufacturing Examples 3-1 to 3-9] Preparation of Block Copolymers

[0113]

[0114] 2 mol of the hard segment prepared in any one of the manufacturing examples 1-1 to 1-3 was added to 1 mol of the urethane soft segment prepared in any one of the manufacturing examples 2-1 to 2-3, and stirred at room temperature (25° C.) for 24 hours. At this time, the equivalent ratio of the isocyanate group of the urethane soft segment to the hydroxyl group of the hard segment was adjusted to 1:1.

[0115] The block copolymers of Production Examples 3-1 to 3-9 are summarized in Table 1 below.

[0116]

Table 1

[0117]

[0118] [Examples 1 to 9] Preparation of adhesive composition

[0119] 25 wt% of a base epoxy resin (YD-128K; bisphenol A epoxy resin, Kukto Chemical Co., Ltd.), 15 wt% of an amine curing agent (PN-23J, Ajinomoto Fine Chemicals), 10 wt% of a multifunctional acrylic compound (Miramer M600; dipentaerythritol hexaacrylate (DPHA; Dipentaerythritol Hexaacrylate), Miyuan), 10 wt% of a thiol compound (KarenzMT PE1; a mixture of pentaerythritol tetra(3-mercaptobutyrate) and pentaerythritol tri(3-mercaptobutyrate), Showa Denko), 1 wt% of a photoinitiator (Irgacure 184, Ciba), 5 wt% of fumed silica (Fumed silica, TS-720, Cabot Corporation), 29 wt % of fused silica (Fused silica, FB-3SDC, Nippon Electric Chemical Co., Ltd.) and 5 wt % of the block copolymer prepared in any one of the preparation examples 3-1 to 3-9 to prepare an adhesive composition (total 100 wt %).

[0120] [Comparative Example 1]

[0121] The preparation method is the same as that of Example 1, except that the contents in Example 1 are changed to 26 wt % of the base epoxy resin, 16 wt % of the amine curing agent, 11 wt % of the multifunctional acrylic compound, 11 wt % of the thiol compound, 30 wt % of the fused silica, and 0 wt % of the block copolymer.

[0122] [Comparative Examples 2 and 3]

[0123] The same method as in Example 1 was used except that the block copolymer was not added in Example 1 and the hard segment of Production Example 1-2 and the soft segment of Production Example 2-2 were added in the same amounts.

[0124] The physical properties of the adhesive compositions prepared in Examples 1 to 9 and Comparative Examples 1 to 3 were evaluated and shown in Table 2 below.

[0125]

Table 2

[0126] Block copolymers Storage stability Adhesion force [kgf] Impact resistance [times] Comparative Example 1 - O 120 5 Comparative Example 2 Production Example 1-2 O 115 8 Comparative Example 3 Production Example 2-2 X 85 7 Example 1 Production Example 3-1 O 118 30 Example 2 Production Example 3-2 O 125 25 Example 3 Production Example 3-3 O 115 15 Example 4 Production Example 3-4 O 130 35 Example 5 Manufacturing Example 3-5 O 127 25 Example 6 Manufacturing Example 3-6 O 118 20 Example 7 Manufacturing Example 3-7 O 110 40 Example 8 Production Example 3-8 O 125 32 Example 9 Production Example 3-9 O 119 25

[0127] As shown in Table 2, it was confirmed that the adhesive compositions according to the embodiments of the present invention all had excellent adhesion and storage stability and excellent impact resistance. In contrast, in the case of Comparative Example 1 not including the block copolymer according to one aspect, or Comparative Examples 2 and 3 containing the soft segment or the hard segment alone, it was confirmed that the impact resistance was very poor.

[0128] That is, as the adhesive composition according to one aspect contains the above-mentioned block copolymer as an impact reinforcing agent, it is confirmed that the impact resistance is improved excellently while having excellent adhesion, and by achieving the physical properties as described above, it can be expected to be usefully applied to the adhesive layer between components such as miniaturized and thinned camera modules that require excellent adhesion even when used in small amounts and also require durability and impact resistance.

[0129] Although the embodiments of the present invention are described in more detail above with reference to the accompanying drawings, the present invention is not necessarily limited to such embodiments, and various modifications can be implemented without departing from the technical concept of the present invention. Therefore, the embodiments disclosed in the present invention are not used to limit the technical concept of the present invention, but are used for illustration, and the scope of the technical concept of the present invention is not limited by such embodiments. The protection scope of the present invention should be interpreted by the attached claims, and all technical concepts falling within the scope equivalent thereto should be interpreted as being included in the scope of the rights of the present invention.

Claims

1. An adhesive composition, wherein: The adhesive composition comprises a block copolymer containing a (meth)acrylate hard segment and a urethane soft segment.

2. The adhesive composition according to claim 1, wherein The (meth)acrylate hard segment contains repeating units derived from C1-7 alkyl (meth)acrylate monomers.

3. The adhesive composition according to claim 1, wherein The number average molecular weight (Mn) of the (meth)acrylate hard segment is 20k to 500 k g / mol.

4. The adhesive composition according to claim 1, wherein The urethane soft segment contains repeating units derived from polyether polyols.

5. The adhesive composition according to claim 1, wherein The number average molecular weight (Mn) of the urethane soft segment is 1000 to 5000 g / mol.

6. The adhesive composition according to claim 1, wherein The block copolymer is a triblock copolymer or a multiblock copolymer comprising two or more hard segments.

7. The adhesive composition according to claim 1, wherein The block copolymer comprises 0.1 to 20 wt % relative to the total weight of the composition.

8. The adhesive composition according to claim 1, wherein The adhesive composition also includes a base epoxy resin and a curing agent.

9. The adhesive composition according to claim 8, wherein The adhesive composition further comprises a multifunctional monomer and a photoinitiator.

10. The adhesive composition according to claim 9, wherein The multifunctional monomer is a multifunctional acrylic compound, a thiol compound or a combination thereof.

11. The adhesive composition according to claim 1, wherein The adhesive composition is a dual-curing adhesive composition.

12. A solidified product, wherein: The cured product is prepared from the adhesive composition according to any one of claims 1 to 11.

13. A block copolymer, wherein: The block copolymer includes a urethane-based soft segment and contains a (meth)acrylate-based hard segment at both ends.

14. The block copolymer according to claim 13, wherein The (meth)acrylate hard segment contains repeating units derived from C1-7 alkyl (meth)acrylate monomers.

15. The block copolymer according to claim 13, wherein The number average molecular weight (Mn) of the (meth)acrylate hard segment is 20k to 500 k g / mol.

16. The block copolymer according to claim 13, wherein The urethane soft segment contains repeating units derived from a polyether polyol and repeating units derived from an alicyclic diisocyanate compound.

17. The block copolymer according to claim 13, wherein The number average molecular weight (Mn) of the urethane soft segment is 1000 to 5000 g / mol.

18. A toughening agent for epoxy adhesive, wherein: The toughening agent for epoxy adhesives comprises the block copolymer according to any one of claims 13 to 17.